2021
DOI: 10.1111/jdv.17857
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and remission rates of self‐reported hidradenitis suppurativa ‐ A prospective cohort study conducted in Danish blood donors

Abstract: Background A large discrepancy between physician-diagnosed and self-reported Hidradenitis suppurativa (HS) exists.Knowledge regarding incidence and remission rates of self-reported HS is missing, but may help bridge the gap in understanding between these two phenotypes.Objectives To determine the incidence and remission rates of self-reported HS, and to what degree these are affected by sex, smoking and BMI.Methods A prospective cohort of 23 930 Danish blood donors. Information on self-reported HS, symptom-loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…The review process was initiated by a literature search, which retrieved a total of 8,259 articles. After removing duplicates, 735 articles were assessed for eligibility, and 46 were ultimately included in the study 7–52 . A flowchart depicting the selection process can be found in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The review process was initiated by a literature search, which retrieved a total of 8,259 articles. After removing duplicates, 735 articles were assessed for eligibility, and 46 were ultimately included in the study 7–52 . A flowchart depicting the selection process can be found in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Seven studies on weight loss's effects on HS were found (Table S1). The designs were three case series, two cohorts, and one cross‐sectional study 7,21–26 . Studies agree on significant improvement in HS severity and a higher likelihood of remission in patients with substantial weight loss.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…HS epidemiology remains a very active area of interest, and numerous papers have been published from different countries including Europe, Africa and the United States 2–4 . A recent Danish study has shown a HS prevalence of 1.8% in 27765 blood donors, 5 and many of the authors have also participated in the article ‘Incidence and remission rates of self‐reported hidradenitis suppurativa ‐ a prospective cohort study conducted in Danish blood donors’ 6 object of the present commentary.…”
mentioning
confidence: 98%